Comparison of open acromioplasty outcomes according to approach type; anterior and lateral - Kayaokay, Kemal; Mirzazade, Cevad; Küçük, Levent; Coşkunol, Erhan (Journal of Surgery and Medicine, 2017)
Aim: Subacromial impingement syndrome appears to be one of the most frequent causes of shoulder pain. Acromioplasty is the surgical intervention modality where conservative treatment no longer gives effect. Even though arthroscopic techniques keep arising popularity, open acromioplasty yet is very often used surgery. Our main goal was to compare clinical success of anterior and lateral open techniques whether or not these techniques affect final range of motion, DASH , UCLA & CONSTANT scores Methods: We assembled 37 regularly followed cases (26 female, 11 male ) over 18 years old, operated between 2014-2016. We then ultimately evaluated comparison among variations such as age, sex, dominant extremity, postoperative follow-up time, approach type, operation duration, acromion type and most recent form where CONSTANT, DASH and UCLA scores , ROM(range of motion) , developed complications were assessed. We divided cases to 2 main groups ; group1 anterior approach and group 2 lateral approach. Comparison throughout this particular study mainly went on these 2 groups. Results: 70.3% (26 cases ) were female , 29.7% (11 cases) were male. Mean age was 57.64 ± 9.17 (avg 45-84years) . 75.6 % (28 cases ) had symptoms on dominant limb. Postoperative mean follow-up 18,49±5.37 months (avg 8-28 months). Mean operation duration was 35 minutes for group 1 and 37 minutes for group 2. No complications were presented. Patients also filled out prepared subjective survey papers at final clinical examination. Mean CONSTANT score was 88.5 for group1 and 83.57 for group 2. Postoperative recovery lasted upon 7.1 ± 3.3 weeks (avg 1-12 week) and 6.6 ± 3.9 weeks (avg 1-14 wk) in group 2. CONSTANT, UCLA and DASH scores were evaluated separately and showed no significant difference in ordinary comparison, whereas very same CONSTANT scores were put to odds ratio calculator and presented surprising result ; according to preoperative-postoperative comparison, anterior approach was predicted that would have had 2.8 times chance to show better results( 80< score) than lateral approach. Same ordinary comparison was performed on UCLA and DASH scores and no significant difference was detected. Although very same odds ratio calculation for UCLA scores appeared to be 2.5 and for DASH it was 1.167. In all three assessment methods anterior approach was more recommendable approach type. Subjective assesments of the patients were as following: 14 patients determined clinically very good and good , 1 patient normal in group 1 , where 16 patients were determined very good amd good , 2 normal and 3 patients poor according to overall scoring . Conclusion: There is no significant difference between anterior and lateral approaches according to ROM, various scorings, hospitalization duration. On the other hand, for subacromial impingement, open acromioplasty is yet highly reliable, convenient method with short surgery time.